Interaction between linker histone H1 and non-histone chromatin protein HMGB1. Issue 1 (2010) - Fonin Fonin, Alexander V. Alexander V.; Stepanenko Stepanenko, Olga V. Olga V.; Kuznetsova Kuznetsova, Irina M. Irina M.; Turoverov Turoverov, Konstantin K. Konstantin K.; Kostyleva Kostyleva, Elena I. Elena I.; Vorobyev Vorobyev, Vladimir I. Vladimir I.
Abstract : The possibility of interaction between linker histone H1 and non-histone chromatin protein HMGB1 was studied by intrinsic UV-fluorescence, far and near-UV CD and light scattering. The obtained data allow us to assume that the increase of histone H1 content in the HMGB1 solutions in a low ionic strength is accompanied by the destruction of HMGB1 associates. The interaction between proteins causes the increase of ordered regions in the protein molecules and the minor changes in their tertiary structure.